The Significant Impact of Ti Addition on the Hot Deformation Behavior of Medium‐Manganese Microalloyed Steel. Issue 9 (10th April 2021) - Dong, Ying; Zhang, Bin; Du, Yu; Du, Lin-Xiu; Misra, Raja Devesh Kumar
Abstract : The constitutive analysis and microstructural characteristics of Ti microalloyed medium‐Mn steel are studied here by hot deformation test in the temperature range of 1123–1473 K and at the strain rates from 0.01 to 10 s −1 based on thermal simulation. Furthermore, the effect of Ti addition on hot deformation behavior is elucidated. The results indicate that the fluctuation of flow stress, which is sensitive to deformation conditions, is a result of dynamic equilibrium between strain hardening and thermally activated work softening. Flow stress constitutive equations for low Ti and high Ti content steels are developed with an average deformation activation energy Q of 456.1 and 350.9 kJ mol −1, respectively. The morphologies of prior austenite grain (PAG) and dynamic recrystallization (DRX) behavior are dramatically influenced by the compression parameters and the Ti content. The PAG size decreases with the increase in the Ti content, which can accelerate the progress in the DRX process. As a result, the refined martensite lath is obtained in the steel with high Ti content. Abstract : The constitutive analysis and microstructural characteristics of Ti microalloyed medium‐Mn steel are studied by a series of hot compression tests. Systematic studies on flow stress behavior, constitutive equations, and hot deformed microstructure under different deformation conditions are conducted. The influence of Ti on dynamic restoration behavior is also studied.